Performance Study Of Potash Alum On Wastewater Treatment System From Biomass Gasifier Water Scrubber - Abidin, Norshahirah Adina Zainol (Universiti Sains Malaysia, 2017)
The performance of potassium alum or also known as potash alum (KAl(SO4)2) as coagulant on treating wastewater from biomass gasifier water scrubber were investigated in a chemical treatment. Potash alum is proven to be capable of removing total suspended solids (TSS), total dissolved solid (TDS), and decrease the turbidity at optimum concentrations. The treatments were performed in a jar apparatus. The rapid mixing was performed in jar test after the potash alum were added in the beaker before the floc were allowed to settle down for 30 min. Before the treatments were started, the initial conditions of wastewater such as pH, temperature, turbidity, TSS, TDS and heavy metals contain in wastewater were being investigated. The presence of heavy metals in the wastewater were being checked by using atomic absorption spectroscopy (AAS). AAS is a spectro-analytical procedure for the quantitative determination of chemical elements using the absorption of optical radiation (light) by free atoms in the gaseous state. At optimum concentrations, the removal efficiency were found to achieve 62.5 and 52.8% for TSS and TDS, respectively.